Spontaneous Healing of a Rectovaginal Fistula Developing after Laparoscopic Segmental Bowel Resection for Intestinal Deep Infiltrating Endometriosis - William Kondo; Reitan Ribeiro; Carlos Henrique Trippia; Monica Tessmann Zomer (Case Reports in Obstetrics and Gynecology)
The surgical treatment of intestinal deep infiltrating endometriosis has an associated risk of major complications such as dehiscence of the intestinal anastomosis, pelvic abscess, and rectovaginal fistula. The management of postoperative rectovaginal fistula frequently requires a reoperation and the construction of a stoma for temporary fecal diversion. In this paper we describe a 27-year-old woman undergoing laparoscopic treatment of deep infiltrating endometriosis (extramucosal cystectomy, resection of the uterosacral ligaments, resection of the posterior vaginal fornix, and segmental bowel resection) complicated by a rectovaginal fistula, which healed spontaneously with nonsurgical conservative treatment.